A Study of Resilience Factors and Coping Strategies for Adolescent Victims of Cyberbullying - Phantong, Kannika; Prasertsin, Ujsara; Sriprasertpap, Khwanying; Charupheng, Monthira (Hatyai Academic Journal, 2021)
The purposes of this research were 1) to study components of resilience and coping strategies for adolescent victims of cyberbullying and 2) to analyze the confirmatory factors. A semi-structured in-depth interview was used in the study. Nine adolescences who experienced cyberbullying were purposively selected as key informants. The study was conducted through qualitative methodology by an analytic-induction interview. The obtained data was then used to develop questions and the analysis process. Three-hundred high-school students aged between 15-19 years old in Matthayom 4-6 were asked to answer the questions. The LISREL version 8.72 was used to assess the construct validity. With each item ranked between 0.67 and 1.00 of an IOC value, the entire test (all items) was validated with 0.867 and 0.817 reliability values respectively. The validation was conducted with 50 high-school students of the same age-range. It was found that there were three components of resilience: self-consciousness, self-adaptability, and self-recovery ability. Each component was tested with ten questions. The model was therefore coherent with the empirical data and related with the Grotberg Framework and with the resilience quotient (RQ) developed by the Department of Mental Health. There were two components in coping with the bullying: problem-focused coping strategies and emotion-focused coping strategies. Each component was tested with eight questions. The model then was coherent with the empirical data and related with the Lazarus & Folkman Framework.